Dispersal of key subplinian–Plinian tephras from Hekla volcano, Iceland: implications for eruption source parameters - Janebo, Maria H.; Thordarson, Thorvaldur; Houghton, Bruce F.; Bonadonna, Costanza; Larsen, Gudrun; Carey, Rebecca J. (Bulletin of Volcanology, 2016)
Hekla is the most active silicic volcano in Iceland, with 18 subplinian–Plinian eruptions since AD 1104. In the period 1970 to 2000, the frequency of such eruptions increased to once every decade. Hekla is currently inflated to above the levels observed prior to the most recent eruptions in 1991 and 2000. The next eruption could pose a hazard to air traffic between North America and Europe because explosive eruptions of Hekla, independent of size, typically start with a subplinian or Plinian phase that produces a sustained ash plume. We present an overview of five of the largest historical Hekla eruptions (taking place in 1104, 1158, 1300, 1693, and 1766). These eruptions cover a compositional range of rhyolite to andesite, previously estimated Volcanic Explosivity Index (VEI) values of 4–5 and are characterised by contrasting wind dispersal (dispersal axes NW–NE). New isopach maps show both greater deposit thicknesses in the proximal region and wider dispersal than previously inferred, resulting in different volume estimates (minimal values ranging between 0.18 and 0.91 km3). New isopleth maps were also compiled and resulted in inferred plume heights of about 13–25 km. These changes in the estimated values of volume and mass eruption rates have large implications on the forecasting and impacts of future Hekla eruptions.